Fine mapping of a supernumerary proleg mutant (ECs‐l) and comparative expression analysis of the abdominal‐A gene in silkworm, Bombyx mori. Issue 5 (27th June 2013) - Chen, P.; Tong, X.‐L.; Li, D.‐D.; Liang, P.‐F.; Fu, M.‐Y.; Li, C.‐F.; Hu, H.; Xiang, Z.‐H.; Lu, C.; Dai, F.‐Y.
Abstract: Patterning and phenotypic variations of appendages in insects provide important clues on developmental genetics. In the silkworm Bombyx mori, morphological variations associated with the E complex, an analogue of the Drosophila melanogaster bithorax complex, mainly determine the shape and number of prolegs on abdominal segments. Here, we report the identification and characterization of the allele responsible for the supernumerary crescents and legs‐like ( E Cs ‐l ) mutant, a model derived from spontaneous mutation of the E complex, with supernumerary legs and extra crescents. Fine mapping with 1605 individuals revealed a ∼68 kb sequence in the upstream intergenic region of B. mori abdominal‐A ( Bmabd‐A ) clustered with the E Cs ‐l locus. Quantitative real‐time PCR (qRT‐PCR) and Western blotting analyses disclosed a marked increase in Bmabd‐A expression in the E Cs ‐l mutant at both the transcriptional and translational levels, compared to wild‐type Dazao . Furthermore, we observed ectopic expression of the Bmabd‐A protein in the second abdominal segment (A2) of the E Cs ‐l mutant. Our results collectively suggest that the 68 kb region contains important regulatory elements of the Bmabd‐A gene, and provide evidence that the gene is required for limb development in abdominal segments in the silkworm.